Control of lipase production by Rhizopus oligosporus under various growth conditions - Nahas, E. (Microbiology Society, 1988)
Some factors influencing the growth and production of extracellular lipase by Rhizopus oligosporus were studied. Highest yields of enzyme were obtained when Tweens were the carbon source. Soybean meal extract supported good growth and enzyme production. Carbohydrates, vegetable oils, proteins or amino acids did not stimulate lipase production. The fungus grew well with carbohydrate- or protein-supplemented media but not with oils, unless emulsified with a non-metabolizable gum. The production of biomass in static cultures was maximum at 35-40°C after 4 d at pH 5.5. The yield of lipase was maximum at 25°C after 3 d at pH 6.5. Shaking cultures enhanced growth but decreased lipase production.
Keywords: triacylglycerol lipase; fungus; growth; nonhuman; rhizopus oligosporus